Parental conflict and social networking sites addiction in Chinese adolescents: The multiple mediating role of core self-evaluation and loneliness. (January 2021) - He, Dan; Liu, Qing-Qi; Shen, Xi
Highlights: Parental conflict is a risk factor for adolescent SNSs addiction. Both core self-evaluation and loneliness mediated the link between parental conflict and SNSs addiction. The two mediate factors mediate the link between parental conflict and SNSs addiction not only parallely but also sequentially. Abstract: Previous research has documented that parental conflict is positively associated with adolescent social networking sites (SNSs) addiction. However, the mediating mechanisms underlying this relation are largely unknown. The current aimed to study investigate the mediation effects of core self-evaluation and loneliness in the association between parental conflict and SNSs addiction. A sample of 1270 Chinese adolescents ( Mage = 14.50, SDage = 1.59, 45% females) completed anonymous questionnaires regarding parental conflict, core self-evaluation, loneliness, and SNSs addiction. The findings revealed that both core self-evaluation and loneliness mediated the link between parental conflict and SNSs addiction. In addition, core self-evaluation and loneliness sequentially mediated the associated between parental conflict and SNSs addiction. The multiple mediation analysis reveals that core self-evaluation and loneliness can not only in parallel, but also sequentially mediate the relation between parental conflict and SNSs addiction. The current study contributes to better understanding how parental conflict can increase the risk of SNSs addiction, and has implications for the prevention and intervention of adolescent SNSs addiction.